ANALISIS VOLATILITAS HARGA SAHAM DENGAN ROA DAN ROE SEBAGAI VARIABEL KONTROL (Studi Pada Perusahaan Yang Terdaftar Dalam Indeks LQ45) - Pomartia, Tiwuk Zadri; JMV, Mulyadi; Rachbini, Widarto (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2018)
The purpose of study is to determine how much the effect of price earning ratio, book value per share and debt to asset ratio on stock price volatility with return on asset ratio and return on equity ratio as control variables. Sample data of this study were 127 data from 26 companies listed in the LQ45 index with the study period from 2012 until 2016. The analysis model uses multiple linear regression with a significance level of 5%. The results explain that price earnings ratio has a negative and significant effect on stock price volatility, book value per share has a negative and significant effect on stock price volatility while the debt to asset ratio does not affect stock price volatility.